Prevention of Social Stigma Related to Coronavirus Disease 2019 (COVID-19) - Arash Aliasghari (Shahrekord University of Medical Sciences, 2021)
As a result of the global crisis related to coronavirus disease 2019 (COVID-19), confusion, anxiety, fear, and some psychological effects have been created among the general population in this global village. Unfortunately, these factors have provoked inappropriate behavior converting the infection to the virus to a social stigma, which can affect the dignity of people died due to COVID-19. In addition to the patient, the stigma can also affect interpersonal relationship among nurses, family members, friends, as well as social relationships. In this critical situation, we need to take care of each other with empathy, which is the key to successfully cope with the issue and prevent social stigma associated with COVID-19. This commentary evaluates the effects of social stigma related to COVID-19 and suggests some practical measures for the world communities to deal with this global public health problem.